Analisis Pengembangan Obyek Wisata Alam di Resort Balik Bukit Taman Nasional Bukit Barisan Selatan - Meizannur Meizannur; Christine Wulandari (Jurnal Sylva Lestari, 2015)
Nasional Bukit Barisan Selatan (TNBBS) is a nature conservation area which has a lot of potential, flora, fauna and natural attractions that have a high value of naturalness. One of the resorts that were recently developed tourist attraction is its natural Resort Balik Bukit. This study aims to: (1) determine the resource potential of nature in Resort Balik Bukit, (2) determine the potential of human resources that exist around the Resort Balik Bukit, (3) determine that management made in the development of natural attractions Behind Hill Resort, and (4) formulating development strategies of natural attractions Resort Balik Bukit TNBBS. The study was conducted for 3 months, from January to March 2013. Data collected through direct observation, interviews, and literature. Data analysis was done in 2 ways descriptive analysis and SWOT by calculating the weight and rating of EFAS and IFAS. The results showed Resort Balik Bukit TNBBS has tourism potential interest to visitors such as Waterfall, River Way Sepapa, Lower Mountains Forest Ecosystem, Flora and Fauna, Nature landscape, and Stone shaped beam. Potential around the Resort Balik Bukit that support community development activities is the ability to make crafts. Management of natural attractions Resort Balik Bukit performed by TNBBS ranging from planning, organizing, implementation, and supervision, but the development is still less than optimal conducted and no other parties are involved. Based on the research results of the most important strategies that can be applied to the Great Hall TNBBS is promoting potentials in Resort Balik Bukit to the tourist market and cooperated with the parties so that the development of natural attractions Resort Balik Bukit can be better. Keywords: Potential of Nature Tourism, SWOT Analysis , Taman Nasional Bukit Barisan Selatan, Resort Balik Bukit